IMPACT OF AN ACTION CYBER CRIME PREVENTION PROGRAMME ON IN-SCHOOL AGED CHILDREN’S ATTITUDE TO CRIME PREVENTION CONCEPTS IN CIVIC EDUCATION AND SOCIAL STUDIES - Amosun, Peter Adewale; Ige, Olugbenga Adedayo (European Scientific Journal, ESJ, 2013)
This study evaluated the impact of a participatory cyber crime prevention programme on inschool aged children’s attitude to cyber crime prevention in Nigeria, consequent on the global annual ranking of Nigeria as one of the most cyber lawless countries by The National White Collar Crime Center and Federal Bureau of Investigation in the United States of America. The study used the participatory action research paradigm to develop an informal cyber crime prevention programme, and further utilized pretest-posttest quasi experimental design to evaluate the impact of the action cyber crime prevention programme on secondary school students’ attitude in Civic Education and Social Studies. The sample of the study comprised two hundred and eighteen students purposefully selected from intact classes in six secondary schools in Nigeria. Percentages, Mean, Standard Deviation and Analysis of Covariance (ANCOVA) were used to analyze the data. Multiple Classification Analysis aspect of ANCOVA was used to determine the magnitude of performances across the groups, while line graph was used to disentangle significant the interaction effects. Results showed that there is significant main effect of treatment on in-school aged children’s attitude to cyber crime prevention in civic education and social studies. Consequent on these, the study recommended the use of Action Cyber Crime Prevention Programme for developing countries experiencing the menace of cyber crimes perpetrated by school-age children.